Human neutralising antibodies elicited by SARS‐CoV‐2 non‐D614G variants offer cross‐protection against the SARS‐CoV‐2 D614G variant. Issue 2 (22nd February 2021) - Lee, Cheryl Yi‐Pin; Amrun, Siti Naqiah; Chee, Rhonda Sin‐Ling; Goh, Yun Shan; Mak, Tze‐Minn; Octavia, Sophie; Yeo, Nicholas Kim‐Wah; Chang, Zi Wei; Tay, Matthew Zirui; Torres‐Ruesta, Anthony; Carissimo, Guillaume; Poh, Chek Meng; et al.
Abstract: Objectives: The emergence of a SARS‐CoV‐2 variant with a point mutation in the spike (S) protein, D614G, has taken precedence over the original Wuhan isolate by May 2020. With an increased infection and transmission rate, it is imperative to determine whether antibodies induced against the D614 isolate may cross‐neutralise against the G614 variant. Methods: Antibody profiling against the SARS‐CoV‐2 S protein of the D614 variant by flow cytometry and assessment of neutralising antibody titres using pseudotyped lentiviruses expressing the SARS‐CoV‐2 S protein of either the D614 or G614 variant tagged with a luciferase reporter were performed on plasma samples from COVID‐19 patients with known D614G status ( n  = 44 infected with D614, n  = 6 infected with G614, n  = 7 containing all other clades: O, S, L, V, G, GH or GR). Results: Profiling of the anti‐SARS‐CoV‐2 humoral immunity reveals similar neutralisation profiles against both S protein variants, albeit waning neutralising antibody capacity at the later phase of infection. Of clinical importance, patients infected with either the D614 or G614 clade elicited a similar degree of neutralisation against both pseudoviruses, suggesting that the D614G mutation does not impact the neutralisation capacity of the elicited antibodies. Conclusions: Cross‐reactivity occurs at the functional level of the humoral response on both the S protein variants, which suggests that existing serological assays will be able to detect both D614 and G614 clades of SARS‐CoV‐2. More importantly, there should be negligible impact towards the efficacy of antibody‐based therapies and vaccines that are currently being developed. Abstract : A single point mutation from aspartic acid (D) to glycine (G) at position 614 of the SARS‐CoV‐2 spike (S) protein, termed D614G, has garnered global attention due to the observed increase in transmissibility and infection rate. Given that a majority of the developing antibody‐mediated therapies and serological assays are based on the S antigen of the original Wuhan reference sequence, it is crucial to determine whether humoral immunity acquired from the original SARS‐CoV‐2 isolate is able to induce cross‐detection and cross‐protection against the novel prevailing D614G variant. In this study, we demonstrated an overall equivalent neutralising capacity against both the D614 and G614 pseudoviruses, suggesting negligible impact towards the efficacy of antibody‐based therapies and vaccines that are currently being developed.